Efficacy of five plant extracts against Black bean aphid, Aphis fabae Scopoli (Hemiptera: Aphididae) - Sirwan Sharif, Gona (Zanco Journal of Pure and Applied Sciences, 2024)
The efficacy of five selected plant extracts: Basil (Ocimum basilicum), Cloves (Syzygium aromaticum), Tarragon (Artemisia dracunculus), Mint (Mentha sp.), and Dill (Anethum graveolens) against Aphis fabae on both nymph and adult stages was evaluated under laboratory conditions. Four concentrations were used 10000, 20000, 50000, and 100000 ppm. The results showed that the maximum mortality percentage of the nymph stage of A. fabae was achieved by basil, tarragon, and clove aqueous extracts at concentrations of 10000 ppm after 72 hours of treatment. Conversely, basil, clove, and tarragon extracts recorded the highest mortality rate of adults under the same experimental conditions. The positive control (Acetamiprid 20%) produced the highest mortality rate after 72 hours of exposure while using distilled water as the negative control resulted in a minimal mortality rate. The LC50 values indicate that basil extract exhibited the highest toxicity for nymphs at 1664.177 ppm after 72 hours, while for adults, tarragon extract was the most toxic at 720.553 ppm at 72 hours.